Pancreas Allograft Transplantation in Dogs with Experimental Diabetes Mellitus - Mendívil Zapata, Rolando (1998)
OBJETIVE : To evaluate the efficacy of pancreatic allograft transplantation (TAP ) in dogs with diabetes mellitus ( DME ) induced by alloxan . METHODS : 63 mongrel dogs were used , of which 33 for the very best experimental conditions , the other 30 were divided into 3 groups of 10 each : a) controls, were only produced DME b ) receptors with DME, the who underwent TAP and c) pancreas donors . RESULTS : The glycemic control was complete in 50% of recipients and partial in 30% , giving an overall efficiency of TAP relative to control 80 %. The survival time was 19.9 + TAP post - 6,2 hours. Pathologic examination showed signs of hyperacute rejection , Major complications were gastrointestinal bleeding , aspiration pneumonia , necrotizing pancreatitis with generalized peritonitis , hypoglycemia and dogs not awakened from anesthesia. CONCLUSIONS : The TAP was effective in controlling blood glucose levels in 80 % of animals , but survival was poor, which could be related to the toxic effect of alloxan and hyperacute rejection. More experimental studies are needed to improve survival .